Brain and Liver Headspace Aldehyde Concentration Following Dietary Supplementation with n‐3 Polyunsaturated Fatty Acids. Issue 11 (10th September 2015) - Ross, Brian M.; Babay, Slim; Malik, Imran
Abstract: Reactive oxygen species react with unsaturated fatty acids to form a variety of metabolites including aldehydes. Many aldehydes are volatile enough to be detected in headspace gases of blood or cultured cells and in exhaled breath, in particular propanal and hexanal which are derived from omega‐3 and omega‐6 polyunsaturated fatty acids, respectively. Aldehydes are therefore potential non‐invasive biomarkers of oxidative stress and of various diseases in which oxidative stress is thought to play a role including cancer, cardiovascular disease and diabetes. It is unclear, however, how changes in the abundance of the fatty acid precursors, for example by altered dietary intake, affect aldehyde concentrations. We therefore fed male Wistar rats diets supplemented with either palm oil or a combination of palm oil plus an n‐3 fatty acid (alpha‐linolenic, eicosapentaenoic, or docosahexaenoic acids) for 4 weeks. Fatty acid analysis revealed large changes in the abundance of both n‐3 and n‐6 fatty acids in the liver with smaller changes observed in the brain. Despite the altered fatty acid abundance, headspace concentrations of C1–C8 aldehydes, and tissue concentrations of thiobarbituric acid reactive substances, did not differ between the 4 dietary groups. Our data suggest that tissue aldehyde concentrations are independent of fatty acid abundance, and further support their use as volatile biomarkers of oxidative stress.